E-commerce www.blonjo.online as Climate Change Campaign by Micro, Small and Medium Business Enterprise - R. Muhammad Amin Sunarhadi; Prabang Setyono; Lia Kusumaningrum; Siti Rahmawati; Sapta Suhardono; Hashfi Hawali Abdul Matin (Universitas Veteran Bangun Nusantara, 2022)
This article describes the development of an e-commerce web-based used to offer micro, small and medium enterprises (MSMEs) products from the community of Indonesia Council for Small Business (ICSB), Sukoharjo Regency. MSMEs entrepreneurs adopt information technology (IT) as marketing their marketing tools. To engage participation in climate change adaptation and mitigation, www.blonjo.online provide positive content from the entrepreneurs as the awareness campaign. Development of www.blonjo.online considers input from ICSB Sukoharjo to identify and situation analysis problems entrepreneurs face in the e-commerce platform. Some mentoring was conducted to increase understanding of climate change issues and their impact on environmental damage, green marketing, photography, and copywriting. Based on the need for information system specification, e-commerce was developed and tested for the design and performance of information systems, then prototyping. MSMEs entrepreneurs upload their climate change campaign in three climate change adaptation and mitigation categories: taking more efficient raw materials, avoiding non-renewable materials in production, and using environmentally friendly packaging.